Making Multiple Money - Зелизер, Вивиана (Journal of Economic Sociology, 2010)
The author considers the fundamental transformations that took place in the process of marking money in the USA in the period from 1870 till 1930-s. Four types of social environment were chosen for the analysis and explanation of the variation models in the conditions and ways of demarcation of money: household, presents from relatives and friends, institutional money and moral money.